The Effect of Using Enjoyable Teaching For gaining More Achievement and Social Efficiency in the Subject of Mathematics for Grade Six Female Students in Jordan - Ramadan, Hadeel Hassan; Abu Sneineh, Odeh Abdeljawad (Journal of Educational and Psychological Sciences, 2020)
This study aims to tackle the effects of using enjoyable and efficient teaching methods, in Mathematics on students’ academic achievement. It also attempts to thoroughly follow pupils’, rising social competency due to enjoying their teachers’ modern and thrilling techniques in class. The study assessed (38) female students, from grade six, the chosen sample followed the highlighted purposes to this study. Then, they were separated into an experimental group, of 20 students that were exposed to the efficient teaching methods And the controlled group, of (18) students were exposed to typical and traditional teaching approaches. To achieve this study’s’ targeted goals and objectives, the lesson plans followed the exciting and efficient teaching methods on summative assessment and a social competency scale were added too, to check their consistency, therefore, they were applied after exposing learners to efficient and exciting teaching methods. The results of this study conveyed a difference, with a significant statistical maker and level of (α=0.05) between the score average of both examined groups, the experimental and controlled groups, in the summative assessment in Mathematics, due to using the modern and efficient teaching techniques. The same significant statistical maker and level was found in both of the mentioned groups’ social competency assessment test. To benefit the trial group, this study suggests certain recommendations, like designing activities that mainly follow efficient and exciting teaching techniques, in other units, in Mathematics for they help to develop students’ potential to achieve higher marks and better their social competency This study also encourages Mathematics teachers to apply practical and efficient teaching methods to have an exciting learning experience.